A Modified Gain Schedulling Controller by Considering the Sparseness Property of UAV Quadrotors - M Qodar Abdurrohman; Reka Inovan; Ahmad Ataka; Hilton Tnunay; Ardhimas Wimbo; Iswanto Iswanto; Adha Cahyadi; Yoshio Yamamoto (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
This work presented the gain scheduling based LQR for Quadrotor systems. From the original nonlinear model, the system is always controllable and observable in various equilibrium points. Moreover, the linearized systems have a unique property that is known as sparse system. Hence, in order to implement the most efficient state feedback controller, post-filter and pre-filter were introduced to transform the state coordinate to decrease coupling between states. Finally, the gain scheduling systems using these facts was proposed. The system behavior was tested using the proposed controller. The numerical studies showed the effectiveness of the controller to achieve desired altitude, attitude, and its ability during the disturbance